Effect of Return On Investment and Return On Equity of Share Return PT Bank Rakyat Indonesia Tbk Between 2011-2020 - Dede Sulastri (Indonesian Financial Review, 2021)
This study aims to determine whether or not there is an effect of Return On Investment on Stock Return and Return On Equity on Stock Return. The company under study is PT. Bank Rakyat Indonesia Tbk. 2011-2020 period. The data used in this research is secondary data. Using descriptive research methods and the data is quantitative. The analytical method used in this research is multiple linear regression analysis with classical assumption test and hypothesis testing. The variables used are Return On Investment (X1) and Return On Equity (X2) on Stock Return (Y). and the coefficient of determination at a significant level of 25.7%. Simultaneously ROI and ROE have no significant effect on Stock Return at PT. Bank Rakyat Indonesia Tbk. 2011-2020 period.